Dynamic changes and prognostic value of glutathione S-transferase alpha in mild cognitive impairment and Alzheimer’s disease - Tang, Yangyang; Li, Ni; Dai, Linyan; Wang, Xingsheng; Lai, Xia (Frontiers in Aging Neuroscience, 2024)
ObjectivesGlutathione S-transferase alpha (GSTα) is an important antioxidant enzyme closely associated with the onset and progression of neurodegenerative diseases. The alterations in GSTα protein levels associated with Alzheimer’s disease and their impact on cognitive abilities remain unclear. Thus, investigating the fluctuations of GSTα protein levels in mild cognitive impairment (MCI) and Alzheimer’s disease (AD) is essential.MethodsDATA were enrolled from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, and we studied healthy individuals (as controls, a total of 54), patients with mild cognitive impairment (345), and patients with Alzheimer’s disease (96) A one-year follow-up was conducted to collect data on the dynamic changes of GSTα protein levels in plasma and primary information data, and to analyze the correlation between the changes in GSTα protein levels before and after the follow-up and cognitive function and its predictive value.ResultsPlasma GSTα protein levels were significantly lower in the AD group than in the CN group (0.94 vs1.05, p = 0.04) and the MCI group (0.94 vs1.09, p < 0.001). Plasma GSTα protein level changes were positively correlated with altered MMSE levels in MCI and AD patients (r = 0.09, p = 0.04). The AUC (95% CI) of the area under the prediction curve of plasma GSTα protein levels for MCI was 0.63 (0.54–0.71), p = 0.02, and the AUC (95% CI) of the area under the prediction curve of plasma GSTα protein levels for AD was 0.74 (0.69–0.80), p < 0.001. At the same time, we plotted ROC curves for the difference in the change of plasma GSTα protein levels after 1 year of follow-up. The results showed that the AUC (95% CI) of the area under the prediction curve of plasma GSTα protein levels change for MCI was 0.76 (0.696–0.83), p < 0.001, and the AUC (95% CI) of the area under the prediction curve of plasma GSTα protein levels change for AD was 0.75 (0.69–0.80), p < 0.001.ConclusionThe findings of the study indicated notable differences in GSTα protein levels among patients with MCI and those with AD after a one-year follow-up period. Furthermore, a positive correlation was observed between changes in GST αprotein levels and the decline in both baseline and cognitive function. This suggests that GSTα protein could potentially act as a biomarker for both MCI and AD, offering fresh insights for early detection and intervention strategies.